2022
DOI: 10.34190/ecsm.9.1.333
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Clothes Shopping and the Influence of Brand Image and Perceived Benefits on Purchase Intention

Abstract: The research around social networks have become increasingly important in recent years because they are a powerful means of communication between different generations, especially the younger ones. Social networks are occupying a privileged place in the marketing and communication of brands, which has been reflected in the increase in sales in various sectors of activity. The present investigation aims to analyze how the relationship between Brand Image and Clothing Purchase Intention is mediated by the Consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Given these results, it was intended to find out which products are most purchased through this digital medium and it was found that they were the mass consumption products (e.g., food, hygiene, household cleaning), followed by those that fall into the category of Fashion and beauty (Table 2). The literature review on purchase intentions drew our attention to the fact that they can be influenced by the gender of consumers (Lopes et al, 2022), so it was considered pertinent to compare means according to this sociodemographic variable. The results revealed that women have higher mean values (M = 4.59; SD = 1.20) when compared to men (M = 4.43; SD = 1.31) with regard to purchase intention, with statistically significant differences [t (1971) = -2.728, p < 0.05].…”
Section: Resultsmentioning
confidence: 99%
“…Given these results, it was intended to find out which products are most purchased through this digital medium and it was found that they were the mass consumption products (e.g., food, hygiene, household cleaning), followed by those that fall into the category of Fashion and beauty (Table 2). The literature review on purchase intentions drew our attention to the fact that they can be influenced by the gender of consumers (Lopes et al, 2022), so it was considered pertinent to compare means according to this sociodemographic variable. The results revealed that women have higher mean values (M = 4.59; SD = 1.20) when compared to men (M = 4.43; SD = 1.31) with regard to purchase intention, with statistically significant differences [t (1971) = -2.728, p < 0.05].…”
Section: Resultsmentioning
confidence: 99%